The incidence of the communicative approach on the level of the speaking skill development in students attending the first year of basic education at the Rudolph Steiner school during the second term, 2007 - 2008 school year - Guerrero Andrade, Maria Eugenia (2014)
This research is specifically concerned with the incidence of the Communicative Approach on the level of the Speaking Skill development in students of first year of education. This work makes a comparison between two groups of students a Control Group which received English with the traditional method and an Experimental Group in which the Communicative Approach was applied. First, it presents a brief description of the school, its history and facilities. Then, information about Communicative Approach, its origins, role of the teacher, and principles, the Speaking Skill, and its development, and finally all the work done with the Experimental Group using Communicative Approach techniques and activities. Communicative Approach let students learn the language through activities related with daily life events that made students participate orally and in a relaxed way. This way students built their knowledge because they were living what they were learning. The Control Group maintained its traditional methodology...